1988
DOI: 10.1111/j.1439-0418.1988.tb00588.x
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory studies on the development, survival, mating behaviour and reproductive capacity of the rice moth, Corcyra cephalonica (Stainton) (Lep., Galleriidae)

Abstract: Development of the rice moth, Corcyra cephalonica (Stainton), from first instar larvae to adults in a whole wheat flour medium, took 40.9 and 43.5 days for males and females, respectively. Adult longevity was 9.1 and 7.0 days for mated and virgin males; 8.3 and 8.0 days for mated and virgin females, respectively. Virgin females laid more eggs than mated ones and as the number of moths per cage increases, the number of eggs decrases. Maximum mating response occurred during the second night after emergence. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

1989
1989
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 6 publications
1
1
0
Order By: Relevance
“…Both sexes were equally affected, since the sexual ratio was close to 0.5 (1% : 1&) on the 6 diets studied. These values were close to those found by Kamel & Hassanein (1967) and Cox et al (1981) and Etman et al (1988), who obtained a sexual ratio close to 1:1.…”
Section: Resultssupporting
confidence: 92%
“…Both sexes were equally affected, since the sexual ratio was close to 0.5 (1% : 1&) on the 6 diets studied. These values were close to those found by Kamel & Hassanein (1967) and Cox et al (1981) and Etman et al (1988), who obtained a sexual ratio close to 1:1.…”
Section: Resultssupporting
confidence: 92%
“…5 days. Etman et al, (2009) also observed that adult longevity was 9.1 and 7.0 days for mated and virgin females, respectively, on wheat flour medium. The fecundity of rice moth, Corcyra cephalonica (Stainton.)…”
Section: Resultsmentioning
confidence: 83%